A Study on the Morphology of Poly(Triaryl Amine)-Based Hole Transport Layer via Solvent Optimization for High-Performance Inverted Perovskite Solar Cells - Xiaoyin Xie; Xi Liu; Chufei Ding; Han Yang; Xueyi Liu; Guanchen Liu; Zhihai Liu; Eun-Cheol Lee (Inorganics)
Poly[bis(4-phenyl) (2,5,6-trimethylphenyl) amine (PTAA), as a hole transfer material, has been widely used in perovskite solar cells (PSCs). However, the optimal solvent for preparing the PTAA solution and coating the PTAA layer is still uncertain. In this work, we investigated three types of organic solvents (toluene, chlorobenzene and dichlorobenzene) for processing PTAA layers as the hole transport layer in PSCs. Based on the experimental verification and molecular dynamics simulation results, all the evidence indicated that toluene performs best among the three candidates. This is attributed to the significant polarity difference between toluene and PTAA, which leads to the formation of a uniform surface morphology characterized by granular protuberances after spin coating. The contact area of the hole transfer layer with the surface aggregation is increased in reference to the rough surface, and the hydrophilicity of the PTAA layer is also increased. The improvement of these two aspects are conducive to the effective interfacial charge transfer. This leads to the generation of more photocurrent. The PSCs employing toluene-processed PTAA exhibit an average power conversion efficiency (PCE) of 19.1%, which is higher than that of PSCs using chlorobenzene- and dichlorobenzene-processed PTAA (17.3–17.9%). This work provides a direct optimization strategy for researchers aiming to fabricate PSCs based on PTAA as a hole transport layer and lays a solid foundation for the development of high-efficiency inverted PSCs.